2013
DOI: 10.1111/clr.12174
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of the resorption rate of deproteinized bovine bone as maxillary sinus graft material on cone beam computed tomography

Abstract: The results indicate that DBB graft volume resorption is approximately (20 ± 10%) following 2-year follow-up. CBCT is a useful radiographic tool to follow-up changes in sinus graft volumes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 30 publications
2
33
0
1
Order By: Relevance
“…In the past, evaluations during implant treatment were primarily performed using panoramic radiography and conventional CT. Recently, however, the use of preoperative and postoperative CBCT has gained popularity, and radiographic assessment by CBCT for volumetric changes in graft bone in maxillary sinus floor augmentation has also been reported [16]. According to our radiographic analysis by CBCT of dental implantation using β-TCP in the present study, we found that the graft volume decreased over time, both at 6 months after surgery and even at 2.5 years after surgery.…”
Section: Discussionsupporting
confidence: 62%
“…In the past, evaluations during implant treatment were primarily performed using panoramic radiography and conventional CT. Recently, however, the use of preoperative and postoperative CBCT has gained popularity, and radiographic assessment by CBCT for volumetric changes in graft bone in maxillary sinus floor augmentation has also been reported [16]. According to our radiographic analysis by CBCT of dental implantation using β-TCP in the present study, we found that the graft volume decreased over time, both at 6 months after surgery and even at 2.5 years after surgery.…”
Section: Discussionsupporting
confidence: 62%
“…The time devoted by Umanjec-Korac S. [14] to explorebone graft volume changes after a sinus floor augmentation was 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…Umanjec-Korac S. et al [14] analyzed the resorption rate of deproteinized bovine bone material used alone as well as mixed with autologous bone chipsas graft material. A retrospective analysis of 29 augmented sinuses in 19 patients was conducted and CBCT scans of the augmented sinuses were obtained pre-and post-operatively up to 2-year followup.The results indicatedsimilar graft volume resorption for both groups of approximately 20 ± 10%.…”
Section: Introductionmentioning
confidence: 99%
“…4 For such cases, sinus lifting procedure is employed frequently in the dental practice with high predictability and well surgical outcomes. 5 Maxillary sinus lifting procedure has become widely accepted as a routine method to improve the bone height before implant placement. [6][7][8] Several sinus floor elevation techniques have been recommended in the literature to overcome these limitations.…”
Section: Introductionmentioning
confidence: 99%